Optimization of solution composition in hexagonal boron nitride crystal growth via the flux method - Janzen, Eli (Kansas State University, 2023)
Hexagonal boron nitride (hBN) is an ultrawide bandgap (>6 eV) semiconductor and 2D material that has attracted much attention due to its unique properties and applications in electronics, optoelectronics, and nanophotonics. In all of these applications, large, high quality single crystals of hBN are required and atmospheric pressure solution growth is a consistent method to achieve this. This study was undertaken to improve this process, accelerate its optimization, and enable creation of devices in a wide range of fields. A new methodology was developed to optimize the boron concentration in hBN solution growth using the CALPHAD (CALculation of PHAse Diagrams) method to rapidly predict the optimal boron concentration for a wide range of solvents. Comparison with experimental results validates its accuracy. Deviations from CALPHAD predictions, confirmed with crystal growth by reusing source material, suggest that the hBN crystal growth process from molten metal solutions is kinetically limited. Reusing source material also substantially improves the yield of boron to hBN, which is especially important when using expensive isotopically pure boron for growth of h¹⁰BN or h¹¹BN. Increasing the nitrogen solubility of the solvent is often attributed to increasing crystal size, but this work digs deeper into the effects of this property. Five different solvents (Ni-Cr, Co-Cr, Fe, Fe-V, and Cu) were tested and the domain area and thickness of crystals they produced were compared versus their nitrogen solubility. The nitrogen solubility did not affect the hBN domain area but the crystal thickness increased with nitrogen solubility. This suggests that, so long as the boron concentration is properly optimized, similar domain sizes can be obtained from any solvent. Furthermore, the thickness of as-grown crystals may be engineered for specific applications by choosing a solvent that naturally grows hBN of the required thickness. Finally, the optimal boron concentration increased with the nitrogen solubility, provides a shortcut for optimizing future solvents, accelerating research. Crystal defects such as stacking faults, dislocations, and impurities are detrimental to device performance, thus it is important to understand their properties and how they can be avoided or eliminated. Oxygen impurities were greatly reduced in the solvent with the introduction of hydrogen gas while carbon impurities may need to react with oxygen to be removed. Regardless, the impurity content in hBN crystals grown from these solvents was below the detection limit of secondary ion mass spectrometry (SIMS) in all cases, suggesting the purity of the process is already sufficient. Three classes of defects were detected using cathodoluminescence (CL) spectroscopy: spots, invisible lines, and wrinkles, which were determined to be color centers, half-inserted planes, and plastic deformation of hBN single crystals, respectively. A combination of Raman, photoluminescence (PL), and CL spectroscopy indicates that hBN crystals grown from Ni-Cr and Co-Cr tend to have fewer defects than those grown from Fe, Fe-V, or Cu. Monoisotopic hBN is especially useful in applications where coherence of phonons is especially important such as sub-wavelength optical microscopy and quantum sensing. Previously, processes were developed to synthesize hBN enriched with either the ¹⁰B or ¹¹B isotopes using naturally abundant ¹⁴N₂. In this work, a new process was developed to extend the capabilities of solution growth to also produce hBN with the ¹⁵N isotope. Raman and PL spectroscopy on these crystals indicate that they are very high quality, on par with crystals grown with ¹⁴N. Furthermore, the effect of the reduced mass on the Raman shift of the E₂[subscript g][superscript high] peak and the energy of the phonon replicas is identified, which is in excellent agreement with theory.
Keywords: Hexagonal boron nitride; Crystal growth